Improving Economic Efficiency Through Asset Management of Information Technology Asset Inventory at PT. Chandra Asri - Mohammad Jamalulael (Green Publisher Indonesia, 2024)
Effective asset inventory is crucial for asset management, allowing organizations to optimize asset use, prevent loss, and ensure readiness. PT. Chandra Asri faces challenges in IT asset management, including incomplete and inconsistent data, hindering operational efficiency. This qualitative study examines the current state of IT asset management at PT. Chandra Asri and highlights the potential benefits and challenges of implementing advanced technologies like RFID, barcodes, and cloud-based systems. Case studies from various sectors demonstrate significant improvements in operational efficiency, cost reduction, and customer satisfaction with these technologies. This research offers valuable insights for practitioners, policymakers, and academics in developing better asset inventory strategies.